2017
DOI: 10.1097/iae.0000000000001342
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Analysis of Pigment Epithelial Detachment Response to Different Anti–vascular Endothelial Growth Factor Agents in Wet Age-Related Macular Degeneration

Abstract: Quantifiable metrics of PED morphology improve with treatment, and PED content becomes hyperreflective, more so on aflibercept. Pigment epithelial detachments respond better in the context of more active disease. More hyporeflective PED content may predispose to better treatment response, especially with aflibercept.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
1
17
1
Order By: Relevance
“…The response to treatment is different than in treatment naïve patients who have new active disease and usually show good outcome with early initiation of anti-VEGF treatment. For treatment naive patients with nAMD related PED, most studies have reported anatomical improvement in terms of reduction in PED height with Bevacizumab [ 10 – 13 ] Ranibizumab [ 10 , 11 , 13 22 ] and Aflibercept [ 10 , 20 22 ]. With Bevacizumab (1.25 mg) treatment, Freeman WR et al showed no statistically significant change in SRF and IRF resorption or visual acuity improvement in PED and non-PED groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The response to treatment is different than in treatment naïve patients who have new active disease and usually show good outcome with early initiation of anti-VEGF treatment. For treatment naive patients with nAMD related PED, most studies have reported anatomical improvement in terms of reduction in PED height with Bevacizumab [ 10 – 13 ] Ranibizumab [ 10 , 11 , 13 22 ] and Aflibercept [ 10 , 20 22 ]. With Bevacizumab (1.25 mg) treatment, Freeman WR et al showed no statistically significant change in SRF and IRF resorption or visual acuity improvement in PED and non-PED groups.…”
Section: Discussionmentioning
confidence: 99%
“…A post hoc subgroup analysis in the HARBOR study of patients presenting with PED at baseline reported PED height reduction and BCVA gain with Ranibizumab across PEDs of all heights but a decrease in vision in eyes with extra-large PEDs treated with higher dose of Ranibizumab [ 19 ]. With aflibercept treatment H J Cho and Balaskas K have reported greater reduction in PED height compared to ranibizumab [ 20 , 22 ] at 1 year. They also noticed improved BCVA at 1 year in both groups but variable correlations to baseline parameters.…”
Section: Discussionmentioning
confidence: 99%
“…They also observed in 6-months follow-up, the mean number of injections and visits were similar in 2 drug groups [23]. On the contrary, Balaskas et al, found a libercept is more effective than ranibizumab according to anatomic and functional results of 3 rd and 12 th months [24].…”
Section: Current Treatment Of Vascularized Pigment Epithelial Detachmentmentioning
confidence: 81%
“…PED height decrement is positively associated with higher baseline PED height, the higher the baseline PED height the more reduction was observed [27]. According to Balascas et al, study, all of baseline values including BCVA, subretinal luid, central macular thickness, PED volume, PED's vertical dimension have prognostic importance [24]. In contrary, there are many studies argued that baseline characteristics of PED have not any in luence on the functional outcomes [23].…”
Section: Current Treatment Of Vascularized Pigment Epithelial Detachmentmentioning
confidence: 98%
“…Optical coherence tomography (OCT) is one particularly crucial technology that has allowed for more accurate characterisation of retinal conditions such as neovascular age-related macular degeneration (AMD). [1][2][3] In AMD structural OCT measures such as macular thickness have been instrumental in confirming response to anti-vegf agents 1 and further research has explored the clinical importance and relevance of other OCT features, such as pigment epithelial detachments, 2 subretinal fluid 3,4 and subretinal fibrosis. 5 Studies that specifically assess the relationship between such structural imaging findings and visual function [6][7][8] provide particularly important information for both research and clinical practice.…”
Section: Introductionmentioning
confidence: 99%